Potential impacts of information disclosure designed to motivate Japanese consumers to reduce carbon dioxide emissions on choice of shopping method for daily foods and drinks. (15th August 2015) - Motoshita, Masaharu; Sakagami, Masaji; Kudoh, Yuki; Tahara, Kiyotaka; Inaba, Atsushi
Abstract: Information disclosure associated with carbon dioxide emissions of goods or services may be useful for stimulating consumers to make choices to reduce carbon dioxide emissions. The scope of this study was to analyze the potential impact of information disclosure on consumer choices of daily shopping method through an internet survey of Japanese residents (2630 subjects). Japanese consumers were shown to have a preference for low carbon dioxide emissions in their choice of daily shopping method. Awareness of responsibility and intention to act were identified as crucial influences on consumer willingness to reduce carbon dioxide. Supporting information such as comparative presentation of the impacts of well-known everyday carbon dioxide reducing activities effectively made consumers more receptive and sensitive to the meanings and consequences of their choices. The provision of quantitative information on the carbon dioxide emissions associated with different shopping methods may prompt consumers to alter their current choices by comparing the benefits of carbon dioxide reductions and time savings with their preferences for certain shopping methods. Highlights: Japanese consumers favor choices in daily shopping that minimize CO2 emissions. Awareness of responsibility and intention to act influence consumer CO2 reductions. Familiarity with reducing CO2 promotes consumers' understanding of its importance. Consumers will shop more from home if CO2 reduction information is more available.